Calidad de vida en urticaria crónica y su relación con el impacto económico y control de la enfermedad en pacientes atendidos en el Hospital Universitario de Monterrey, México - Arias Cruz, Alfredo; González Díaz, Sandra Nora; Macías Weinmann, Alejandra; Ibarra Chávez, Jesús Arturo; Sánchez Guerra, Daniel; Leal Villarreal, Lucía; Salinas Díaz, María del Rocío (2018)
Abstract Background: Chronic urticaria (CU) manifests itself with hives and sometimes angioedema. Physical and social discomfort worsens patient quality of life. CU has an important impact on patients’ economy. Objective: To evaluate the relationship of quality of life (QoL) with economic burden and chronic urticaria control of in patients treated at our center. Methods: Cross-sectional, descriptive, observational study. We included CU-diagnosed adult patients. The CU-Q2oL and UCT questionnaires in Spanish and the economic burden and comorbidities questionnaire developed by our center were applied. A sample size of 36 patients was calculated. Results: 36 patients were included, out of which 58.3% were females. Mean age was 39.9 ± 15.6 years. Regarding QoL, 66.7% of patients reported being "A little" aﬀ ected, 25% "Somewhat" and 8.3% "A lot", and its relationship with monthly income yielded a p-value of 0.017. 38.9% of patients reported having a monthly income of less than $ 5000 pesos. When disease control was compared with the CU-Q2oL, a signiﬁ cant diﬀ erence was obtained for questions concerning itching. Conclusion: There was association between the quality of life of patients with chronic urticaria and monthly income, the lower the income, the more will the quality of life be aﬀ ected. Furthermore, greater CU control was observed to reduce the negative eﬀ ects on quality of life caused by itching.